Parameter of constitutional regularity control in the face of health emergencies: Conflicts of the Mexican constitutional model in times of covid-19 - Moreno-Reynaga, Martín (DIXI, 2022)
One of the modifications in Mexican law consists of the recognition of the parameter of control of constitutional regularity by the Supreme Court of Justice of the Nation, which hierarchically recognizes international human rights treaties with the Constitution. This produced a material and procedural modification in Mexican constitutional law, beginning the era of the time of rights. However, due to the health emergency caused by sars-CoV2, the effectiveness of the regularity parameter decreased due to the restrictions and suspensions of rights that were ordered, and the exercise of human rights was affected by a health emergency situation. In this paper, we will investigate the effects of the covid-19 crisis on the regularity control parameter, specifying the problems caused by the sanitary emergency. And based on the national and inter-American human rights construction, we will define what measures Mexico should adopt to strengthen the parameter of regularity without disproportionately diminishing the exercise of human rights.